Associations of [18F]-APN-1607 Tau PET Binding in the Brain of Alzheimer’s Disease Patients With Cognition and Glucose Metabolism - Lu, Jiaying; Bao, Weiqi; Li, Ming; Li, Ling; Zhang, Zhengwei; Alberts, Ian; Brendel, Matthias; Cumming, Paul; Lu, Huimeng; Xiao, Zhenxu; Zuo, Chuantao; Guan, Yihui; et al. (Frontiers in Neuroscience, 2020)
Molecular imaging of tauopathies is complicated by the differing specificities and off-target binding properties of available radioligands for positron-emission-tomography (PET). [18F]-APN-1607 ([18F]-PM-PBB3) is a newly developed PET tracer with promising properties for tau imaging. We aimed to characterize the cerebral binding of [18F]-APN-1607 in Alzheimer’s disease (AD) patients compared to normal control (NC) subjects. Therefore, we obtained static late frame PET recordings with [18F]-APN-1607 and [18F]-FDG in patients with a clinical diagnosis of AD group, along with an age-matched NC group ([18F]-APN-1607 only). Using statistical parametric mapping (SPM) and volume of interest (VOI) analyses of the reference region normalized standard uptake value ratio (SUVR) maps, we then tested for group differences and relationships between both PET biomarkers as well as their associations with clinical general cognition. In the AD group, [18F]-APN-1607 binding was elevated in widespread cortical regions (P< 0.001 for VOI analysis, family wise error-corrected P< 0.01 for SPM analysis). The regional uptake in AD patients correlated negatively with mini-mental state examination (MMSE) score (frontal lobe: R= -0.632, P= 0.004; temporal lobe: R= -0.593, P= 0.008; parietal lobe: R= -0.552, P= 0.014; insula: R= -0.650, P= 0.003; cingulum: R= -0.665, P= 0.002) except occipital lobe (R= -0.417, P= 0.076). The hypometabolism to [18F]-FDG PET in AD patients also showed negative correlations with regional [18F]-APN-1607 binding in some signature areas of AD (temporal lobe: R= -0.530, P= 0.020; parietal lobe: R= -0.637, P= 0.003; occipital lobe: R= -0.567, P= 0.011). In conclusion, our results suggested that [18F]-APN-1607 PET sensitively detected tau deposition in AD, and that individual tauopathy correlated with impaired cerebral glucose metabolism and cognitive function.